Ectopic expression of Aspergillus flavus uricase and URAT1 in therapeutic cells promotes intracellular degradation of uric acid in hyperuricemic mice - Yuzhong Feng; Jiazhen Cui; Xuan Huang; Yupeng Li; Haolong Dong; Xianghua Xiong; Gang Liu; Qingyang Wang; Huipeng Chen (PLoS ONE, 2026)
Uricase-based drugs excel at treating refractory hyperuricemia and tumor lysis syndrome by directly degrading uric acid but are limited by immunogenicity. Here, we engineered RAW264.7 macrophages with ectopic co-expression of Aspergillus flavus uricase and murine urate anion transporter 1 (URAT1), forming a “transport-degradation” system: URAT1 actively transports uric acid into cells for intracellular degradation. Recombinant lentiviral vectors carrying target genes were transfected into RAW264.7 cells, followed by puromycin screening. In vitro assays showed that the engineered macrophages nearly completely degraded uric acid (from 556.0 ± 37.0 μmol/L to 0.7 ± 0.6 μmol/L) at 72 h. URAT1 inhibition with benzbromarone abolished uric acid degradation in URAT1-expressing cells. In both acute dietary-induced and chronic genetic hyperuricemic mouse models, RAW-afUri-URAT1 exerted robust and sustained uric acid-lowering activity, maintaining serum uric acid at 77.14 ± 37.48 μmol/L on day 16 in yeast extract gavaged mice and normalizing serum uric acid to 76.2 ± 15.9 μmol/L in liver uricase conditional knockout mice, both significantly superior to the rebound levels observed in mice treated with Rasburicase (143.19 ± 38.21 μmol/L and 142.4 ± 17.4 μmol/L, respectively; P < 0.05). Safety assessments in dietary-induced hyperuricemia mice showed no obvious abnormalities in liver or renal function, and significantly reduced hyperuricemia-related production of inflammatory cytokines (IL-1β, IL-6, TNF-α), Immunogenicity assays showed undetectable anti-uricase antibodies in RAW-afUri-URAT1 treated mice but high level of antibodies in rasburicase treated mice. This engineered macrophage system shows potent, durable uric acid-lowering efficacy, with low immunogenicity and good biosafety, offering a promising strategy for hyperuricemia therapy.